Pathologic response and survival after neoadjuvant chemotherapy with or without pertuzumab in patients with HER2-positive breast cancer: the Neopearl nationwide collaborative study - Fabbri, Agnese; Nelli, Fabrizio; Botticelli, Andrea; Giannarelli, Diana; Marrucci, Eleonora; Fiore, Cristina; Virtuoso, Antonella; Scagnoli, Simone; Pisegna, Simona; Alesini, Daniele; Sini, Valentina; Orlandi, Armando; et al. (Frontiers in Oncology, 2023)
Purpose: Clinical trials have shown a significant increase in pathologic complete response (pCR) with the addition of pertuzumab to neoadjuvant chemotherapy for patients with early-stage HER-2 positive breast cancer. To date, limited studies have examined comparative outcomes of neoadjuvant pertuzumab in real-world setting. The Neopearl study aimed to assess comparative real-life efficacy and safety of neoadjuvant pertuzumab for these patients. Methods: We conducted a nationwide retrospective analysis involving 17 oncology facilities with a certified multidisciplinary breast cancer treatment committee. We identified patients with HER-2 positive stage II-III breast cancer treated with neoadjuvant chemotherapy based on trastuzumab and taxanes with or without pertuzumab. All patients underwent breast surgery and received a comprehensive cardiologic evaluation at baseline and after neoadjuvant treatment. Patients who received the combination of pertuzumab, trastuzumab, and chemotherapy constituted case cohort (PTCT), whereas those treated with trastuzumab and chemotherapy accounted for control cohort (TCT). The pCR rate and 5-year event free survival (EFS) were the primary outcomes. Secondary end-points were rates of conversion from planned modified radical mastectomy (MRM) to breast conservation surgery (BCS) and cardiotoxicities. Results: From March 2014 to April 2021, we included 271 patients, 134 (49%) and 137 (51%) in TCT and PTCT cohort, respectively. Positive axillary lymph nodes and stage III were more frequent in PTCT cohort. The pCR rate was significantly increased in patients who received pertuzumab (49% vs 62%; OR 1.74, 95%CI 1.04-2.89) and with HER-2 enriched subtypes (16% vs 85%; OR 2.94, 95%CI 1.60-5.41). After a median follow-up of 5 years, the 5-year EFS was significantly prolonged only in patients treated with pertuzumab (81% vs 93%; HR 2.22, 95%CI 1.03-4.79). The same analysis performed on propensity score matched population showed concordant results. On univariate analysis, only patients with positive lymph nodes were found to benefit from pertuzumab for both pCR and 5-year EFS. The rates of conversion from MRM to BCS and cardiologic toxicities did not differ between the cohorts. Conclusion: Our findings support previous data on improved outcomes with the addition of pertuzumab to trastuzumab-based neoadjuvant chemotherapy. This benefit seems to be more significant in patients with clinically positive lymph nodes.